The preparation of a novel eco-friendly methylene Blue/TiO2/PVC composite film and its photodegradability. Issue 4 (4th March 2021) - Zhang, Yan; Shi, Zaifeng; Sun, Tianyi; Zhang, Dashuai; Zhang, Xiaopeng; Lin, Xiaoxue; Li, Chen; Wang, Lili; Song, Junjun; Lin, Qiang
ABSTRACT: A novel photodegradable Methylene Blue (MB)/TiO2 /PVC film was prepared. The physical and mechanical properties, hydrophilicity, and the thermal stability of the film before irradiation were characterized. The photodegradability test was performed by using gel permeation chromatography (GPC), infrared spectroscopy (FT-IR), ultraviolet-visible spectroscopy (UV-vis), and scanning electron microscopy (SEM). Compared with TiO2 /PVC, MB/PVC, and PVC, the MB/TiO2 /PVC film showed the higher photodegradability. The weight loss rates of TiO2 /PVC, MB/PVC, and MB/TiO2 /PVC films after irradiation for 30 h were 8.94%, 15.84%, and 27.55%, respectively, while that of PVC was only 2.12%. The decline rates of Mw and Mn of MB/TiO2 /PVC (MB 2 wt%, TiO2 1 wt%) were 35.68% and 65.38%, respectively. Due to the excellent degradability and usability of the MB/TiO2 /PVC film, the photocatalytic technology is a feasible and effective way to solve "white pollution". GRAPHICAL ABSTRACT: